Design of haul road lighting system. Part III: Application - Karmakar N.C.; Aruna M.; Rao Y.V.; Yaragatti U.K.R. (My University, 2025)
The design of haul road illumination systems based on a scientific approach is very important. Improperly planned lighting systems may provide unsatisfactory illumination and may also incur higher costs. This paper describes illumination systems designed for two haul roads using the computer programs developed in earlier stages of this work. System performances and cost are compared with the existing illumination system. Designs based on the developed programs show total potential cost savings of approximately 26% and 48% for the two systems.